Aperture-adjustable graded porous carbon material as well as preparation method and application thereof
By using tripotassium ethylenediaminetetraacetate and sodium phytate as raw materials, combined with template method and self-activation method, nitrogen and phosphorus co-doped graded porous carbon materials with ordered pore structure and large specific surface area were prepared, and the existing solutions were solved The problem of difficulty in regulating the pore size of porous carbon materials has significantly improved the electrochemical performance of the material.
Patent Information
- Application Number
- CN202411664751.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
AI Technical Summary
The pore structure of existing pore carbon materials is single, and the pore size control cannot be achieved. The preparation method is time-consuming, complex operation and high energy consumption. The material has a small surface area, a wide pore size distribution, and the pore structure is prone to collapse, making it difficult to meet the efficient material transmission. need.
Tripotassium ethylenediaminetetraacetate and sodium phytate are used as the main raw materials, and the temperature-raising and calcining are carried out through the template method and the self-activation method to achieve the preparation of the graded porous carbon material co-doped with nitrogen and phosphorus. The material exhibits an orderly pore structure. , large specific surface area and structural stability.
Successfully prepared a graded porous carbon material with adjustable pore size, with an orderly channel structure, large specific surface area and structural stability, effectively avoiding channel collapse, significantly improving the electrochemical performance of the material, and is suitable for devices such as supercapacitors and zinc ion capacitors. .
Smart Images

Figure CN119503793A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon materials, and specifically relates to a graded porous carbon material with adjustable pore size, and a preparation method and application thereof. Background Art
[0002] Porous carbon materials have shown broad application prospects in many fields due to their unique structures and properties such as high specific surface area, excellent stability, and flexible and adjustable pore structure, as well as advantages such as cheap and readily available raw materials and relatively simple preparation processes. In the prior art, activation technology is often used to prepare porous carbon materials. The basic raw materials must first be carbonized, and after cooling, an activator is added to perform a high-temperature activation step. However, this preparation method is time-consuming, complex to operate, and relatively energy-intensive.
[0003] The patent with publication number CN 110182800 A discloses a method for preparing activated carbon based on potassium salt of ethylenediaminetetraacetic acid. The method uses a single potassium salt of ethylenediaminetetraacetic acid to be successively calcined at high temperature, acid washed, washed with water and dried to obtain activated carbon for adsorption and catalysis based on activated carbon; however, the pore structure of the activated carbon prepared by the method is relatively simple, and the pore size cannot be controlled. The patent with publication number CN 108529587A discloses a method for preparing phosphorus-doped biomass hierarchical porous carbon material and its application. The method uses biomass as a carbon source, phytate as a template and a phosphorus dopant to prepare a hierarchical porous carbon material, but the surface area is small, the pore size distribution is wide, the pore structure is easy to collapse, and there are few active sites on the surface, which makes it difficult to quickly absorb the infiltrated liquid or gas to achieve efficient material transfer. Summary of the invention
[0004] The purpose of the present invention is to provide a graded porous carbon material with adjustable pore size and a preparation method and application thereof, so as to overcome the shortcomings of the prior art, use tripotassium ethylenediaminetetraacetate as a main raw material, as a carbon source and a nitrogen source at the same time, and additionally introduce sodium phytate as a template and a dopant, and successfully prepare the graded porous carbon material through a programmed temperature rise and high-temperature self-activation process. The graded porous carbon material exhibits the characteristics of orderly pore structure, large specific surface area and stable structure, effectively avoids pore collapse, can be used in the field of devices such as supercapacitors and zinc ion capacitors, can achieve higher electrochemical performance as an electrode material, and can significantly improve the problem of poor electrochemical performance of the material.
[0005] In order to achieve the above object, the technical solution of the present invention is:
[0006] In the first aspect, the present invention provides a graded porous carbon material with adjustable pore size, wherein the carbon material is a nitrogen-phosphorus co-doped carbon material, wherein the nitrogen-phosphorus co-doped carbon material has a graded porous structure of micropores and mesopores, and the graded porous structure is a three-dimensional network structure assembled by micropores and mesopores penetrating each other.
[0007] In some other embodiments, the nitrogen content of the nitrogen-phosphorus co-doped carbon material is 1%-2.5%, and the phosphorus content is 0.1-0.3%;
[0008] Preferably, the nitrogen content is 2.01% and the phosphorus content is 0.25%.
[0009] In some other embodiments, the specific surface area of the carbon material is ≥1851.9 m 2 g -1 , total pore volume ≥1.02cm 3 g -1 ;
[0010] Preferably, the specific surface area is 2015.4m 2 / g, and the total pore volume is 1.64m 2 / g;
[0011] Alternatively, the pore size of the micropores is less than 2 nm, and the pore size of the mesopores is 2 to 10 nm.
[0012] The present invention combines the template method with the self-activation method, uses tripotassium ethylenediaminetetraacetic acid as the main raw material, and additionally introduces sodium phytate as a template agent to successfully prepare a hierarchical porous carbon material with adjustable pore size. In this process, tripotassium ethylenediaminetetraacetic acid plays the role of a carbon source, and can achieve self-doping of nitrogen elements. The more common dipotassium ethylenediaminetetraacetic acid can enhance the stability of the prepared porous carbon material. Among them, the potassium element in the tripotassium ethylenediaminetetraacetic acid will undergo high-temperature self-activation to further etch the carbon material matrix, which can make the material produce more pore structures.
[0013] After sodium phytate is introduced as a template, it can be used as a salt template in the activation process and form a pore structure after acid washing. At the same time, the sodium element can further etch the carbon material during the high-temperature activation process to form a richer pore structure. At the same time, sodium phytate can also be used as a dopant to achieve phosphorus doping of the material. However, if the mixing ratio of tripotassium ethylenediaminetetraacetate and sodium phytate is too high, the pore size of the material will be too large; if it is too low, the amount of phosphorus doping may be reduced.
[0014] The nitrogen-phosphorus co-doped carbon material prepared by the present invention has the characteristics of orderly pore structure, large specific surface area and stable structure, which effectively avoids pore collapse. This rich pore structure can provide an effective channel for the diffusion and transfer of molecules and ions.
[0015] In a second aspect, the present invention provides a method for preparing the pore size adjustable graded porous carbon material according to the first aspect, comprising the following steps:
[0016] (1) mixing tripotassium ethylenediaminetetraacetate and sodium phytate, dissolving the mixture in water to form a mixed slurry, and drying the mixture to obtain a mixed powder;
[0017] (2) calcining the mixed powder to obtain a black powder;
[0018] (3) The black powder is sequentially subjected to acid treatment, water washing and drying to obtain a graded porous carbon material with adjustable pore size.
[0019] In some other embodiments, in step (1), the mass ratio of tripotassium ethylenediaminetetraacetate to sodium phytate is (1-5):1;
[0020] Preferably, the mass ratio of tripotassium ethylenediaminetetraacetate to sodium phytate is 2:1;
[0021] Or, the water content of the mixed powder is less than 5%;
[0022] The drying temperature is 100-120°C and the drying time is 5-10h;
[0023] Preferably, the drying temperature is 110° C. and the drying time is 6 hours.
[0024] In some other embodiments, in step (2), the calcination conditions are: in a nitrogen atmosphere, first at 400-500° C., keep warm for 0.5-2 h, and the heating rate is 1-5° C. / min; then, continue to heat to 700-900° C., keep warm for 2-4 h, and the heating rate is 1-5° C. / min; the nitrogen gas flow rate is 30-120 ml / min;
[0025] Preferably, the calcination conditions are: in a nitrogen atmosphere, first at 450°C, keep warm for 1 hour, and the heating rate is 5°C / min; then, continue to heat to 800°C, keep warm for 2 hours, and the heating rate is 5°C / min; the nitrogen gas flow rate is 100ml / min.
[0026] The inventors found in the course of their research that the two-step programmed temperature calcination method is more conducive to the regulation of the pore structure of the material. First, the temperature is raised to 400-500°C, and the material becomes molten, which promotes the further uniform mixing of tripotassium ethylenediaminetetraacetic acid and the template agent sodium phytate. In the subsequent high-temperature activation stage, the potassium element in the tripotassium ethylenediaminetetraacetic acid and the sodium element in the sodium phytate will undergo self-activation to further etch the matrix of the carbon material, producing more pore structures. In this calcination process, self-doping and self-activation are achieved, and the preparation of nitrogen-phosphorus co-doped hierarchical porous carbon materials can be achieved without the introduction of new dopants and activators; at the same time, controllable adjustment of the pore size is achieved. In addition, the two-step programmed temperature calcination method adopted in the present invention can increase the output of hierarchical porous carbon, and effectively avoid the unnecessary consumption or waste of part of the raw materials in the pickling stage due to insufficient activation of the raw materials.
[0027] In some other embodiments, in step (3), the acid used for pickling is one or more of hydrochloric acid, sulfuric acid or nitric acid; the concentration of the acid is 1-3 mol / L, and the pickling time is> 10 h;
[0028] Preferably, the acid is hydrochloric acid, and the concentration of hydrochloric acid is 2 mol·L -1 .
[0029] In some other embodiments, in step (3), the water washing is performed until the pH value of the filtrate is 6-7;
[0030] The drying is performed by vacuum drying at 50-80°C for 10-12 hours;
[0031] Preferably, the vacuum drying temperature is 60° C. and the drying time is 12 h.
[0032] The present invention achieves self-activation and self-doping of materials and controllable adjustment of material pore size by optimizing the composition of raw materials and two-step programmed temperature calcination method, and prepares a graded porous carbon material with adjustable pore size co-doped with nitrogen and phosphorus. The material exhibits the characteristics of orderly pore structure, large specific surface area and stable structure, and effectively avoids pore collapse. The introduction of nitrogen and phosphorus elements can not only effectively improve the wettability of the material, but also increase the chemical adsorption capacity of the material to zinc ions.
[0033] In a third aspect, the present invention provides an application of the pore size-adjustable graded porous carbon material described in the first aspect in a carbon-based energy storage material.
[0034] In some other embodiments, the energy storage material is a capacitor or a battery; preferably, the capacitor comprises a supercapacitor or a zinc ion capacitor.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] (1) The present invention combines template carbonization with high-temperature activation and adopts a two-stage calcination, wherein the first step of calcination is conducive to ensuring the integration of the carbonaceous precursor and the template agent and is conducive to the subsequent carbonization and activation; the second step of high-temperature calcination is conducive to ensuring the full progress of carbonization and activation.
[0037] (2) The activation source in the present invention is the potassium and sodium elements contained in the material itself, and the activation temperature directly affects the formation and stability of the pore structure. When the activation temperature is low, the pore structure is narrow and the effective pore structure is insufficient, resulting in a low zinc storage capacity of the material; when the activation temperature is high, the degree of graphitization of the product increases, causing the pores of the porous carbon material to collapse and shrink.
[0038] (3) The pore size adjustable hierarchical porous carbon material provided by the present invention has high industrial and commercial value. The prepared hierarchical porous carbon material has excellent electrochemical performance, which is conducive to improving the discharge specific capacity and discharge stability under high current density. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0040] Figure 1 This is a scanning electron microscope image of the hierarchical porous carbon material in Example 1 of the present invention;
[0041] Figure 2 The nitrogen adsorption-desorption curves of the graded porous carbon materials in Examples 1-3 of the present invention;
[0042] Figure 3 is the pore size distribution curve of the graded porous carbon material in Examples 1-3 of the present invention;
[0043] Figure 4 This is a constant current charge and discharge diagram of the graded porous carbon material of Examples 1-3 of the present invention. DETAILED DESCRIPTION
[0044] The present invention is further described below with reference to specific examples. The reagents used in the present invention are all commercially available products unless otherwise specified.
[0045] Example 1
[0046] Mix ethylenediaminetetraacetic acid tripotassium salt and sodium phytate in a mass ratio of 1:2, place in a 50ml beaker, add 10ml deionized water and stir for 20min, then dry at 110℃. Grind the dried mixed sample, put it into a nickel boat, place it in a tube furnace, and heat it from 25℃ to 450℃ at a heating rate of 5℃ / min under the protection of flowing nitrogen, keep it warm for 1h, then continue to heat it to 800℃, keep it warm for 2h, and then cool it naturally to room temperature; pickle the carbonized sample obtained in the previous step with hydrochloric acid solution, soak it for more than 10h, then filter and wash it, wash it repeatedly with deionized water, and finally dry it at 60℃ to obtain graded porous carbon material.
[0047] Figure 1 The scanning electron microscope image of the prepared hierarchical porous carbon material. Figure 1 It is observed that the hierarchical porous carbon material has a large number of pore structures, and the pore structure is a three-dimensional network structure assembled by micropores and mesopores penetrating each other.
[0048] Example 2
[0049] Mix ethylenediaminetetraacetic acid tripotassium salt and sodium phytate in a mass ratio of 1:2, place in a 50ml beaker, add 10ml deionized water and stir for 20min, then dry at 110℃. Grind the dried mixed sample, put it into a nickel boat, place it in a tube furnace, and heat it from 25℃ to 450℃ at a heating rate of 5℃ / min under the protection of flowing nitrogen, keep it warm for 1h, then continue to heat it to 700℃, keep it warm for 2h, and then cool it naturally to room temperature; pickle the carbonized sample obtained in the previous step with hydrochloric acid solution, soak it for more than 10h, then filter and wash it, repeatedly wash it with deionized water, and finally dry it at 60℃ to obtain a graded porous carbon material.
[0050] Example 3
[0051] Mix ethylenediaminetetraacetic acid tripotassium salt and sodium phytate in a mass ratio of 1:2, place in a 50ml beaker, add 20ml deionized water and stir for 20min, then dry at 110℃. Grind the dried mixed sample, put it into a nickel boat, place it in a tube furnace, and heat it from 25℃ to 450℃ at a heating rate of 5℃ / min under the protection of flowing nitrogen, keep it warm for 1h, then continue to heat it to 900℃, keep it warm for 2h, and then cool it naturally to room temperature; pickle the carbonized sample obtained in the previous step with hydrochloric acid solution, soak it for more than 10h, then filter and wash it, wash it repeatedly with deionized water, and finally dry it at 60℃ to obtain a graded porous carbon material.
[0052] Figure 2 These are nitrogen adsorption-desorption curves of the graded porous carbon materials in Examples 1-3 of the present invention. The obtained porous carbon materials have a large nitrogen adsorption capacity.
[0053] Figure 3 is the pore size distribution curve of the graded porous carbon material in Examples 1-3 of the present invention. The graded porous carbon material in Examples 1-3 has abundant micropores and mesopores. In addition, the obtained porous carbon contains not only micropores below 2nm, but also mesopores of 2 to 10nm. The porous material is calculated by the BET method to have a diameter of ≥1851.9m 2 g -1 , total pore volume ≥1.02cm 3 g -1 ; The maximum specific surface area of Example 1 is 2015.4m 2 g -1 , with a total pore volume of 1.6 cm 3 g -1 .
[0054] The hierarchical porous carbon material prepared in Examples 1 to 3 was used as the positive electrode material, the conductive carbon black Super P was used as the conductive agent, and PTFE was used as the binder. The positive electrode material: conductive agent: binder were mixed and ground evenly at a mass ratio of 8:1:1 to prepare a slurry with an active material loading of 1 mg / cm 2The thin film was dried to obtain the positive electrode sheet, and a glass fiber membrane was used as the separator, a zinc sheet with a thickness of 80 μm was used as the negative electrode, and a 3M zinc perchlorate aqueous solution was used as the electrolyte to form a zinc ion capacitor and was tested.
[0055] The test conditions for zinc ion capacitors are:
[0056] The assembled zinc ion capacitor was subjected to constant current charge and discharge tests on the Blue Electric Battery Test System. The test voltage range was 0.1-1.9V and the test current density was 0.1-50A g -1 .
[0057] The assembled zinc ion capacitor was subjected to cyclic voltammetry test using an electrochemical workstation. The test voltage range was 0.1-1.9 V and the test scan rate was 5-1000 mV s -1 . Conduct comparative analysis on the test data.
[0058] Figure 4 The constant current charge and discharge diagram of the graded porous carbon material of Examples 1-3 of the present invention is shown in FIG. Figure 4 It is observed that at the same current density, the sample of Example 1 has a -1 At the current density, the specific capacity reaches 184.63 mAh g -1 ; at 5000mAg -1 The discharge current can be stable at a low current density and the specific capacity can still reach 119.91 mAh g -1, It is much higher than other implementation modes, which shows that Example 1 has a higher specific capacity and better zinc storage performance.
[0059] Comparative Example 1
[0060] The difference from Example 1 is that sodium phytate is omitted and only tripotassium ethylenediaminetetraacetic acid is used to prepare the porous carbon material. The other preparation steps are exactly the same as those in Example 1.
[0061] Comparative Example 2
[0062] The difference from Example 1 is that the calcination temperature is changed to a one-stage calcination, that is, the temperature is raised to 800° C. and kept at this temperature for 2 hours to prepare the porous carbon material. The other preparation steps are exactly the same as those in Example 1.
[0063] The properties of the porous carbon materials prepared in the examples and comparative examples of the present application are shown in Table 1:
[0064] Table 1 Properties of porous carbon materials
[0065]
[0066]
[0067] As shown in Table 1, the specific surface area of Example 1 measured by the BET method is 2015.4 m 2 g -1 , with a total pore volume of 1.64 cm 3 g -1 , while the surface areas of Examples 2 and 3 are 1964.5m 2 g -1 and 1.02cm 3 g -1 、1851.9m 2 g -1 and 1.55cm 3 g -1 Compared with the examples, the specific surface areas and pore volumes of comparative examples 1 and 2 both show lower values.
[0068] When evaluating the specific capacity performance at different current densities, among the samples of the examples, Example 3 exhibited the smallest specific capacity at a current density of 200 mA g-1, i.e., 116.72 mAh g -1 , but this value is still higher than the corresponding values in all the samples of Comparative Examples 1 and 2. Furthermore, at a high current density of 5000 mAg-1, the specific capacity of the samples of Examples 1-3 also significantly surpasses that of the comparative samples. Therefore, whether the current density is at a low or high level, the performance of the samples of the examples is significantly better than that of the comparative samples.
[0069] Based on the above research, it is shown that: the present invention uses trimethyl ethylenediaminetetraacetic acid and sodium phytate as raw materials, and adopts self-sacrificial template technology and self-activation technology to successfully prepare hierarchical porous carbon materials with high specific surface area and high mesoporous properties. The pore structure of the material can be customized by finely controlling the mass ratio of the activator to the raw material and the activation temperature and other parameters, thereby greatly enhancing the adsorption efficiency and capacitance characteristics of the porous carbon. The porous carbon material shows excellent performance in the fields of supercapacitors, zinc ion capacitors and zinc ion batteries.
[0070] The above content is only a demonstration of a preferred embodiment of the present invention and does not constitute any form of exclusive limitation on the present invention. Any technician with relevant professional knowledge can make necessary adjustments or innovations based on the above disclosed technical details to develop other embodiments with equivalent functions. As long as these adjustments or innovations do not deviate from the core technical solution of the present invention, they are deemed to be within the technical protection scope of the present invention, including but not limited to slight changes to the embodiments, equivalent replacements and adaptive adjustments.
Claims
1. A graded porous carbon material with adjustable pore size, characterized in that: The carbon material is a nitrogen-phosphorus co-doped carbon material, and the nitrogen-phosphorus co-doped carbon material has a hierarchical porous structure of micropores and mesopores, and the hierarchical porous structure is a three-dimensional network structure assembled by micropores and mesopores penetrating each other.
2. The pore size adjustable graded porous carbon material according to claim 1, characterized in that: The nitrogen content of the nitrogen-phosphorus co-doped carbon material is 1%-2.5%, and the phosphorus content is 0.1-0.3%; Preferably, the nitrogen content is 2.01% and the phosphorus content is 0.25%.
3. The pore size adjustable graded porous carbon material according to claim 1, characterized in that: The specific surface area of the carbon material is ≥1851.9m 2 g -1 , total pore volume ≥1.02cm 3 g -1 ; Preferably, the specific surface area is 2015.4m 2 / g, and the total pore volume is 1.64m 2 / g; Alternatively, the pore size of the micropores is less than 2 nm, and the pore size of the mesopores is 2 to 10 nm.
4. A method for preparing a graded porous carbon material with adjustable pore size according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) mixing tripotassium ethylenediaminetetraacetate and sodium phytate, dissolving the mixture in water to form a mixed slurry, and drying the mixture to obtain a mixed powder; (2) calcining the mixed powder to obtain a black powder; (3) The black powder is sequentially subjected to acid treatment, water washing and drying to obtain a graded porous carbon material with adjustable pore size.
5. The method for preparing a graded porous carbon material with adjustable pore size according to claim 4, characterized in that: In step (1), the mass ratio of tripotassium ethylenediaminetetraacetate to sodium phytate is (1-5):1; Preferably, the mass ratio of tripotassium ethylenediaminetetraacetate to sodium phytate is 2:1; Or, the water content of the mixed powder is less than 5%; The drying temperature is 100-120°C and the drying time is 5-10h; Preferably, the drying temperature is 110° C. and the drying time is 6 hours.
6. The method for preparing a graded porous carbon material with adjustable pore size according to claim 4, characterized in that: In step (2), the calcination conditions are: in a nitrogen atmosphere, first at 400-500° C., keep warm for 0.5-2 h, and the heating rate is 1-5° C. / min; then, continue to heat to 700-900° C., keep warm for 2-4 h, and the heating rate is 1-5° C. / min; the nitrogen gas flow rate is 30-120 ml / min; Preferably, the calcination conditions are: in a nitrogen atmosphere, first at 450°C, keep warm for 1 hour, and the heating rate is 5°C / min; then, continue to heat to 800°C, keep warm for 2 hours, and the heating rate is 5°C / min; the nitrogen gas flow rate is 100ml / min.
7. The method for preparing a graded porous carbon material with adjustable pore size according to claim 4, characterized in that: In step (3), the acid used for pickling is one or more of hydrochloric acid, sulfuric acid or nitric acid; the concentration of the acid is 1-3 mol / L, and the pickling time is >10h; Preferably, the acid is hydrochloric acid, and the concentration of hydrochloric acid is 2 mol·L -1 .
8. The method for preparing a graded porous carbon material with adjustable pore size according to claim 4, characterized in that: In step (3), the water washing is performed until the pH value of the filtrate reaches 6-7; The drying is performed by vacuum drying at 50-80°C for 10-12 hours; Preferably, the vacuum drying temperature is 60° C. and the drying time is 12 h.
9. Use of the pore-size adjustable graded porous carbon material according to any one of claims 1 to 3 in carbon-based energy storage materials.
10. The use according to claim 9, characterized in that: The energy storage material is a capacitor or a battery; preferably, the capacitor comprises a supercapacitor or a zinc ion capacitor.
Citation Information
Patent Citations
Preparation method of phosphor doped biomass graded porous carbon material and application thereof
CN108529587A
Method for preparing activated carbon based on ethylenediaminetetraacetic acid dipotassium salt dihydrate
CN110182800A